Transitioning from Secondary Level (8 – 12) To Higher Institution Entry Towards Enhancing Curriculum Design: A Case of The Namibian Education System - Hamunyela, Hilma Nangula; Kakambi, William Mafelelezo (Advances in Social Sciences Research Journal, 2024)
This study examines the critical transition from secondary education to higher institutions in Namibia, focusing on grades 8-12 and entry into higher education. It uses a framework that highlights the interplay between Senior High School (SHS) profiles, entry requirements, transitioning, and curriculum redesign. The research addresses key issues, such as public universities' entry criteria, SHS graduates' preparedness for university life, and the relationship between entry requirements and transitioning readiness. Additionally, it explores how SHS profiles influence this transition and its implications for curriculum redesign. By reviewing existing literature and collecting quantitative and qualitative data, the study aims to offer insights that inform interventions and policy reforms. The findings are intended to guide educational stakeholders, policymakers, and practitioners in improving the transition process, promoting academic success and overall development for Namibian students.